Monetary Policy and Financial Stability. (Policy Papers; Policy Paper ;, 2015)
The issue of using monetary policy for financial stability purposes is hotly contested. The crisis was a reminder that price stability is not sufficient for financial stability, financial crises are costly, and policy should aim to decrease the likelihood of crises, not only rely on dealing with their repercussions once they occur. It is clear that well-targeted prudential policies (including micro and macroprudential regulation and supervision) should be pursued actively to attenuate the buildup of financial risks. The question is whether monetary policy should be altered to contain financial stability risks. Should it lend a hand by temporarily raising interest rates more than warranted by price and output stability objectives? Keeping rates persistently higher is also possible, but more costly.